CAPITAL FORMATION AND HEALTH OUTCOMES IN MIDDLE-INCOME COUNTRIES - Felix Aberu; Kunle Bankole Osinusi; Kareem Abiodun Arikewuyo; Nurudeen Abiodun Lawal (Jurnal Ekonomi dan Bisnis Airlangga)
Introduction: Understanding how much a country’s health system spends on infrastructure, machinery, and types of equipment is crucial for policymaking and analysis. Although health systems continue to be labor-intensive, capital has been increasingly important in producing health services in recent decades. Considering the growing importance of diagnostic and therapeutic types of equipment, as well as the recent rise of information, computers, and technology in healthcare services being capital intensive, hence, it is imperative to determine the impacts of capital formation on health outcomes in middle-income countries.